Response of Two Cultivars of Faba Bean (Vicia Faba L.) to Different Levels of Phosphorus Fertilizer - Aznor Nazim Saleh; Saja Baker Hassan; Ibrahim Ali Ameen (Andalasian International Journal of Agriculture and Natural Sciences (AIJANS), 2025)
A field experiment was conducted during the winter season (2023–2024) in a private field located in Kirkuk Governorate. The study was implemented as a factorial experiment using a Randomized Complete Block Design (RCBD) with three replications. The results and differences among means were analyzed using Duncan’s Multiple Range Test (DMRT) at a 5% probability level. The experiment aimed to evaluate the response of two faba bean (Vicia faba L.) cultivars (Spanish and local) to five phosphorus fertilizer levels (0, 25, 50, 75, and 100 kg ha-1), applied in two splits. The results showed that the fifth phosphorus level (P5) significantly improved plant height (58.667 cm plant-1), number of branches (6.833 branches plant-1), number of leaflets (40.89 leaflets plant-1), number of flowers (30.33 flowers plant-1), number of pods (27.33 pods plant-1), and single plant yield (188.83 g plant-1). The fourth phosphorus level (P4) also led to significant improvement in all studied traits, with values of plant height (58.667 cm plant-1), number of branches (6.166 branches plant-1), number of leaflets (41.071 leaflets plant-1), number of flowers (31.33 flowers plant-1), number of pods (28.33 pods plant-1), and single plant yield (190.00 g plant-1). No significant differences were observed between the two cultivars. However, significant interactions were found, particularly for the combination A1P5 (Spanish cultivar x fifth phosphorus level), which excelled in plant height (63.00 cm plant-1), number of branches (7.000 branches plant-1), and number of leaflets (42.35 leaflets plant-1). Additionally, the interaction A2P4 (local cultivar x fourth phosphorus level) showed superiority in number of flowers (31.33 flowers plant-1), number of pods (28.66 pods plant-1), and single plant yield (193.67 g plant-1). Meanwhile, the interaction A2P3 (local cultivar x third phosphorus level) was superior in total yield (30.00 kg 1000 m-2).